Simple Isolation and characterization of P-coumaric acid from Cynodon dactylon Linn. (Pers) - A.Viswanath; A.Lakshamana Rao; P.Srinivasa Babu (International Journal of Pharmacy and Analytical Research, 2022)
P-coumaric acid is a non-flavonoid phenolic acid and is a major constituent of the species Cynodon dactylon Linn. (Pers.). In this study isolation of p-coumaric acid was achieved by preparative TLC and the compound thus isolated was characterised by Ultraviolet, Mass and H1 NMR spectral analysis. Mass spectral data shows molecular ion peak of m/z=164.2. A simple method of isolation was reported in this study for identification of P-coumaric acid as a potent antioxidant and anticancer agent prevailed in different commonly available plant species.